Analisa Penambahan Jalur Circuit D pada Taxiway di Bandar Udara Internasional I Gusti Ngurah Rai - Bali - Simaremare, Faprilia; Bunahri, Rifqi Raza; Arta, Deddy Novie Citra; Kona, Musri (Politeknik Penerbangan Jayapura, 2023)
At every airport there is always something called a taxiway, the Runway Connecting Facility (taxiway) is a certain path within the airport location that connects the runway (runway) with the parking runway (apron) in the terminal building area and vice versa, consisting of an exit taxiway , parallel taxiway and high speed taxiway. Taxiway Functions as a connecting facility, so the taxiway in its planning must meet provisions such as the distance between the center line of the taxiway and the center line of the runway, width of the taxiway, wheel clearance, slope and visibility and finally the taxiway strip. In this research, qualitative methods were used to obtain results. By implementing additional circuits on the taxiway, it lightens the load on the CCR on circuit C and the cable route from the CCR on the south side is more efficient and easier to handle troubleshooting on the cable route. In the process of adding circuits to taxiway lights that need to be paid attention to is the preparation work for the application for making airport passes, the worker implementer makes a Method of Working Plan (MOWP) for detailed work and work methods, submits materials for approval. Work implementation must comply with regulations and Standard Operating Procedures (SOP).